Seasonal variations in the North Atlantic Oscillation and the breeding success of arctic-nesting geese - Boyd, Hugh (Wildfowl, 2013)
Long-term studies of 18 populations of eight goose species breeding from arctic Canada to western Siberia have recorded annual variation in the breeding success of geese as the percentage of juveniles seen in autumn. Regression of the annual breeding success data on seasonal values of the North Atlantic Oscillation (NAO) suggest that the passage and intensity of weather systems across eastern North America and northwest Europe have influenced the breeding success of most of these populations. Replacing the NAO by mean sea level pressure (MSLP) at Reykjavik gave similar results. Geese breeding close to the centre of the Icelandic Low appeared to show less response to the NAO than those at greater distances from Iceland. While the NAO indices may be useful for forecasting the breeding success of a population in that year, sea surface temperature changes, which fluctuate more slowly, may be better predictors of goose breeding success over several years.